Compact Structure and Low Losses for Wilkinson Power Divider at 9400MHz Frequency for X-Band Antenna System - Arief Budi Santiko; Novita Dwi Susanti; Taufiqqurrachman Taufiqqurrachman (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexThis paper presents design and implementation 2-way Wilkinson power divider at 9400 MHz frequency which matched to 50Ω transmission line. This design applies Microstrip line with Roger Duroid 5880 Substrate and uses software simulation (ADS 2011) to help the design. This Wilkinson power divider designed at 9400MHz for use on Antenna X-Band Radar System. The desire objective is a power divider can be used in compact circuit board with low insertion loss and good matching for all ports. The dimension of the devices after fabrication is 30mm x 35mm. The voltage standing wave ratio (VSWR) for all port for both dividers is less than 1.33,  Forward transmission the devices as divider or the split power ratio (S21 and S31)is about -2.522dB, reverse transmission the devices as combiner (S12 and S13) is about -2.861dB. The isolation between the both output ports shows a good isolation, less than -11.271dB. The overall result of simulation and fabrication show a fairly good result.